Study on Thickness of Low Carbon Steel in Rapid Cooling Process: A Short Review - Siti Noradila, Abdullah; Norazlianie, Sazali; Ahmad Shahir, Jamaludin (Penerbit UMP, 2020)
For any process that engaged with changes of chemical properties and physical is a heat treatment process by cooling or heating a metal. The technique for heat treatment includes, case hardening, annealing, tempering and precipitation strengthening, quenching and tempering. The mechanical properties like hardness, toughness and ductility can be altered by intense heat treating on steel to produce different mechanical properties. This matters with the carbon content in low carbon steel such as mild steel with above 0.4% carbon, in Medium carbon steel with above 0.8% carbon, and in High Carbon Steel with up to 2% carbon content in steels. To change the characteristics of metals and alloys is by heat treatment process where by altering the diffusion and cooling rate within its microstructure to make them suitable for any kind of usage by changing the grain size at different phases and changing the molecular arrangement.